Electrospun Nanofibers: Connecting Regenerative Medicine and Biomaterials - J, Nirmal Kumar; D, Akiladevi (Journal of Neonatal Surgery, 2025)
Electrospinning is a well-documented and best-supported process for the nanofibrous scaffolds with the biomimetic attributes needed for regenerative tissue engineering. Electrospun nanofibers were implemented with novel biomaterials to significantly enhance their biological, mechanical, and functional characteristics appropriate for tissue engineering and drug delivery purposes. The review outlines the composition and the methods for the preparation of electrospun nanofibers, loaded with various biomaterials based on different natural and synthetic polymers, biomolecules and the surface modification techniques, which improve biocompatibility and therapeutic potency. Moreover, it emphasizes practical bio fabrication methods, drug-loading strategies and functionalization techniques for the advancement of nanofibers in regenerative medicine. We critically discuss recent developments in particular applications including wound healing, bone and cartilage regeneration, neural tissue engineering and cardiovascular therapies. However, a series of shortcomings including scalability, mechanical stability, and controlled biodegradability limits their translation into the clinic. Future works should focus on exploring novel fabrication approaches, personalized medicine principles, and eventually, scale-up production to iterate between the gap from the bench science to the clinical relevance.